Overcoming bud dormancy in apple trees: chilling effect combined with use of budburst inductor - Anzanello, Rafael (2020)
The overcoming bud dormancy in apple trees occurs after an increase of chilling hours in autumn/winter. If the environment does not supply the need for cold plants, budburst inductors are used to overcome dormancy. The objective of this study was to evaluate the overcoming of bud dormancy of apple trees by combining the effect of cold and the use of a budburst inductor. The standard budburst inductor for apple tree cultivation (Dormex® 1% + Mineral Oil 4% - D/OM) was used in the Royal Gala (RG) cultivar after the variety received different cold times. RG cuttings were collected in April/2016 and submitted to D/OM treatment after 0, 100, 200, 300, 400, 500 and 600 CH. A control treatment was included, applying only chilling at 7.2 ºC. In the control treatment, the RG cultivar overcome the dormancy with 549 CH after regression analysis (to 70% budburst range). When tested D/OM combined with cold, the products were not efficient to overcome dormancy after 0, 100 and 200 CH, reaching approximately 50% of budburst. However, when D/OM was applied after 300, 400, 500 and 600 CH, the plants responded with a high budburst rate (above 90% of budburst). In this case, overcoming dormancy (70% of budburst) with D/OM was achieved after 255 CH. It is concluded that the D/OM will have an effect only if the environment supplies 46.4% or more of the genotype chilling requirement in the field.